2020
DOI: 10.1002/biof.1669
|View full text |Cite
|
Sign up to set email alerts
|

Exosome: From leukemia progression to a novel therapeutic approach in leukemia treatment

Abstract: Exosomes, as small vesicles, are released by tumor cells and tumor microenvironment (cells and function as key intercellular mediators and effects on different processes including tumorigenesis, angiogenesis, drug resistance, and evasion from immune system. These functions are due to exosomes' biomolecules which make them as efficient markers in early diagnosis of the disease. Also, exosomes have been recently applied in vaccination. The potential role of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 187 publications
0
5
0
Order By: Relevance
“…Exosomes derived from tumor cells, including leukemia cells, are a rich source of tumor antigens; these antigens originate from parental cells and reflect the tumor content and activities of these parental cells [27,28]. TEX carrying tumor-associated antigens can act as potent inducers of the immune response [29].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from tumor cells, including leukemia cells, are a rich source of tumor antigens; these antigens originate from parental cells and reflect the tumor content and activities of these parental cells [27,28]. TEX carrying tumor-associated antigens can act as potent inducers of the immune response [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the key role of exosomes in haematological malignancies 31,32 . Recent evidence supports the role of leukaemia‐derived exosomes (LEXs) in cancer growth, as well as the treatment of human haematological diseases.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies demonstrated the key role of exosomes in haematological malignancies. 31,32 Recent evidence supports the role of leukaemia-derived exosomes (LEXs) in cancer growth, as well as the treatment of human haematological diseases. Leukaemia-derived exosomes interacting with B and T cells, monocytes, natural killer (NK) cells and granulocytes create an immunoinhibitory environment to help the escape of leukaemia cells from the immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…As reported above, circulating sEVs cargo has been deeply analyzed to detect potential shuttled leukemia markers ( 41 ). Despite the recurring availability of leukemic cells in myeloid leukemias in either BM and/or PB, many groups have conducted studies aiming to improve the sensitivity of the analysis and to reduce the number of invasive and painful BM biopsy ( 42 ).…”
Section: Sevs As Shuttle Of CML Markersmentioning
confidence: 99%